Botanicum medicinale : a modern herbal of medicinal plants - Whitlock, Catherine (Cambridge, Massachusetts : MIT Press, 2020)
A beautifully illustrated, informative, and engaging guide to 100 plants used for medicinal purposes. Remedies derived from plants are the world's oldest medicines. Used extensively in China, India, and many African countries, herbal medicine has become increasingly popular in the West along with other holistic and alternative therapies. Botanicum Medicinale offers a modern guide to 100 medicinal plants, featuring beautiful, full-color botanical illustrations and informative, engaging text.
Packing a punch -- Marijuana matters -- Curcumin Conundrum -- A most potent poppy -- Barking up the right tree.
Includes index.
Keywords: Medicinal plants; Botany, Medical